Gas prices in the UK : markets and insecurity of supply - Wright, P (Oxford Institute for Energy Studies, 2006)
The current debate about UK gas prices is curious for the fact that two of the most commonly-heard explanations for the unprecedented price levels in November 2005, UKCS depletion and bad behaviour in continental Europe, are refutable entirely on logical grounds – without reference to any empirical data whatsoever. The depletion of UK gas production means that the UK started to require net imports again in 2004 and probably to a greater extent in 2005. However, the mere fact of requiring imports should not mean raging prices. Many countries, for example, import gas and to a much greater extent than the UK in 2005.